Applying the Markov chain theory to analyze the attacking actions between FC Barcelona and Manchester United in the European Champions League final - Liu, T.; Hohmann, A. (International Journal of Sports Science and Engineering, 2013)
Several researchers have applied Markov chain methods in sport game analysis. This study analyzed the European Champions League final between Manchester United and FC Barcelona based on a first order Markov chain model. The results describe important passing strategies and tactical connections between certain players from each team.